Problem-solving learning influence on physics learning outcomes based on logical thinking ability - Haris Mahmudi; Muhardjito Muhardjito; Sentot Kusairi (Momentum: Physics Education Journal, 2019)
Problem solving learning is designed to develop students’ ability in solving scientific problem. The purpose of this study is to test the effectiveness of problem solving model on students’ learning outcomes and logical thinking ability. It employed a quasi-experiment with a 2x2 factorial design. The subject was Tenth graders of SMKN 6 Malang. Randomly, it determined two classes of control class and two classes of experimental class. The instrument of this research was logical thiniing test instrument and Physics learning outcome instrument. In addition, it used lesson plan on static fluid as an instrument. Normality and homogenity testing were employed before testing the formulated hypothesis. It employed Liliefors for normality testing and Bartlett for homogenity testing. To test the hypothesis, this research employed Two-ways of ANAVA and Scheffe testing. The results show that (1) Physics learning outcomes of students who learnt by means of problem-solving learning strategy is higher than students who learnt by means of conventional one. (2) It affirms the interaction between problem-solving learning strategy and logical thinking ability of students on Physics learning outcomes. (3) Physics learning outcomes of students who learnt by means of problem-solving learning strategy with high logical thinking ability is higher than students who learnt by means of conventional one. (4) Physics learning outcomes of students who learnt by means of problem-solving learning strategy with low logical thinking ability is higher than students who learnt by means of conventional one.